Pengaruh Work-Life Balance dan Burnout terhadap Kepuasan Kerja Mahasiswa Paruh Waktu Universitas Muhammadiyah Kalimantan Timur - Akhmad Ridwan; Praja Hadi Saputra; Nur Endah Ramayanti (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This study aims to investigate the role of work-life balance and burnout in influencing job satisfaction in part-time students. This study adopted a quantitative approach and conducted a survey through questionnaires to collect responses from 160 employees who were also students at Universitas Muhammadiyah Kalimantan Timur. Based on data analysing using multiple linear regression, the results of this study indicate that the work-life balance of part-time students has a significant effect on their job satisfaction. However, for the burnout variable, there was no effect on the job satisfaction of part-time students at Universitas Muhammadiyah Kalimantan Timur. The results of this study provide practical implications that part-time students need to pay attention to work-life balance (including study) because it will have an impact on their satisfaction at work.